Successful Treatment of Recurrent Airway Stenosis With Paclitaxel‐Coated Balloons: A Case Report - Paola Gutierrez‐Gallegos; Linh H. Vu; Alejandra Yu Lee‐Mateus; Milan Malla; Sofia Valdes‐Camacho; Bryan F. Vaca‐Cartagena; Alanna Barrios‐Ruiz; Bastien A. Valencia‐Sanchez; Elise N. Anderson; Sebastian Fernandez‐Bussy; David Abia‐Trujillo (Respirology Case Reports)
ABSTRACT Although current treatment strategies for nonmalignant airway stenosis may offer short‐term relief, their effectiveness is limited by high recurrence rates, often requiring additional procedures. While paclitaxel‐coated balloons (PCB) have demonstrated effectiveness in treating stenosis across various vascular and nonvascular conditions, their evidence in recurrent airway stenosis remains limited. Here, we present the case of a 35‐year‐old female with bronchial stenosis who underwent multiple bronchoscopic interventions, all of which were complicated by restenosis. Following the addition of a PCB to the therapeutic regimen, the patient achieved sustained airway patency.